2008
DOI: 10.1074/jbc.m706173200
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 Signaling Can Regulate Growth Factor Activation of p44/42 Mitogen-activated Protein Kinases through Protein Phosphatase 2A

Abstract: . 1). The mTORC1 complex comprises mTOR, raptor, mLST8, PRAS40, and controls initiation of translation of ribosomal proteins and several proteins that regulate cell cycle. Activation of ribosomal S6K1 after mitogen stimulation is dependent on mTORC1 (2). Cap-dependent translation is facilitated by mTORC1's phosphorylation and inactivation of 4E-BP1, the suppressor of eukaryotic initiation factor 4E (3, 4). The emerging picture places mTORC1 in a central role in which it senses mitogenic stimuli and amino acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 61 publications
4
19
0
Order By: Relevance
“…In agreement, others have shown that mTORC1 can control the phosphorylation of downstream effectors (e.g. p70 S6 kinase, Erk) via PP2Ac (33)(34)(35). In fact, by immunoprecipitation, mTORC1 physically associated with KPNA1 in a complex that included its associated phosphatase PP2Ac.…”
Section: Discussionsupporting
confidence: 52%
“…In agreement, others have shown that mTORC1 can control the phosphorylation of downstream effectors (e.g. p70 S6 kinase, Erk) via PP2Ac (33)(34)(35). In fact, by immunoprecipitation, mTORC1 physically associated with KPNA1 in a complex that included its associated phosphatase PP2Ac.…”
Section: Discussionsupporting
confidence: 52%
“…For example, ERK1/2 can induce p90 RSK -catalyzed phosphorylation and inactivation of TSC2, resulting in increased mTOR signaling and S6K activation independent of PI3K (46,56,57). Conversely, rapamycin has been shown to diminish growth factor-induced ERK activation in some cells, an effect that may involve mTOR modulating ERK phosphorylation through PP2A (55). Several findings suggest that these interactions are minimal or absent in the MTAL, at least with respect to NGFinduced inhibition of NHE1 and HCO 3 Ϫ absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies using cell systems that enable constitutive activation and/or knockdown of S6K will be required to establish directly a role for S6K in NHE1 regulation. Additional mTOR-associated proteins, such as protein phosphatase 2 (25,54,55), also could be involved in mTOR regulation of NHE1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…8). Furthermore, mTOR activity was found to be required for maximal ERK activation following IR treatment (48), reported to be potentially mediated by mTOR regulation of protein phosphatase 2A activity on ERK (26). The lack of a pronounced biphasic translation response in highly transformed cells is likely the result of a largely constitutively active mTOR signaling pathway and increased basal ERK activity.…”
Section: Discussionmentioning
confidence: 99%